Semut Subfamili Myrmicinae di Suaka Alam Maninjau Utara Selatan, Kabupaten Agam, Sumatera Barat - Susan Septriani; Henny Herwina; Mairawita Mairawita (Universitas Andalas, 2015)
Research about inventory of ants Myrmicinae (Hymenoptera: Formicidae) in Nature Reserve Maninjau Utara-Selatan, Agam, West Sumatra was conducted from June to December 2015 by using the